Framework of plasma physics - Hazeltine, Richard D.; Waelbroeck, Francois L. (Oxford: Westview Press, 2004)
This book provides an excellent introduction to the fundamental physics of plasmas, which comprise most of the matter in the universe. It is based on lectures that were used for an introductory plasma course at the graduate level.
Appendix A1-A4, 307-314p.; Bibliography 315-319p.; Index 320-326p.
Keywords: Plasma physics; Physics